Cytogenetic landscape of paired neurospheres and traditional monolayer cultures in pediatric malignant brain tumors. Issue 7 (23rd December 2014) - Zhao, Xiumei; Zhao, Yi-Jue; Lin, Qi; Yu, Litian; Liu, Zhigang; Lindsay, Holly; Kogiso, Mari; Rao, Pulivarthi; Li, Xiao-Nan; Lu, Xinyan
Abstract: Background: New therapeutic targets are needed to eliminate cancer stem cells (CSCs). We hypothesize that direct comparison of paired CSCs and nonstem tumor cells (NSTCs) will facilitate identification of primary "driver" chromosomal aberrations that can serve as diagnostic markers and/or therapeutic targets. Methods: We applied spectral karyotyping and G-banding to matched pairs of neurospheres (CSC-enriched cultures) and fetal bovine serum-based monolayer cultures (enriched with NSTCs) from 16 patient-derived orthotopic xenograft mouse models, including 9 medulloblastomas (MBs) and 7 high-grade gliomas (HGGs), followed by direct comparison of their numerical and structural abnormalities. Results: Chromosomal aberrations were detected in neurospheres of all 16 models, and 82.0% numerical and 82.4% structural abnormalities were maintained in their matching monolayer cultures. Among the shared abnormalities, recurrent clonal changes were identified including gain of chromosomes 18 and 7 and loss of chromosome 10/10q (5/16 models), isochromosome 17q in 2 MBs, and a new breakpoint of 13q14 in 3 HGGs. Chromothripsis-like evidence was also observed in 3 HGG pairs. Additionally, we noted 20 numerical and 15 structural aberrations that were lost from the neurospheres and found 26 numerical and 23 structural aberrations that were only present in the NSTCs. Compared with MBs, the neurosphere karyotypes of HGG were more complex, with fewer chromosomal aberrations preserved in their matching NSTCs. Conclusion: Self-renewing CSCs in MBs and pediatric HGGs harbor recurrent numerical and structural aberrations that were maintained in the matching monolayer cultures. These primary chromosomal changes may represent new markers for anti-CSC therapies.